Perception and use of the Child's Health Handbook by professionals and mothers: an interactionist approach - Anniely Rodrigues Soares; Anna Tereza Alves Guedes; Daniele de Souza Vieira; Rafaella Karolina Bezerra Pedrosa; Beatriz Rosana Gonçalves de Oliveira Toso; Neusa Collet; Altamira Pereira da Silva Reichert (Universidade Federal do Ceará, 2022)
Objective: to understand the perception of health professionals and mothers about the Children's Handbook. Methods: qualitative study, developed in Family Health Units, with 25 professionals and 11 mothers of children under three years old by means of semi-structured interviews. The empirical material was submitted to Inductive Thematic Analysis and interpreted in the light of Symbolic Interactionism. Results: Child Health Handbook was seen as a multi-professional and intersectoral tool that allows continuity of care, guides the professional's conduct and the care of the child's family. However, it was still seen as a vaccination card. As for use, weaknesses were mentioned during home visits and in professionals' records. In addition, mothers only used it when they took the child to the health service. Conclusion: professionals and mothers presented distinct opinions about the Child Health Notebook. Some considered it as an extension of the medical record and others as a tool like the child's card, being used by specific professionals and at specific times. Contributions to practice: the data reveal meanings and perceptions of the health team and mothers about the Child's Health Handbook and its use, bringing contributions to the scientific knowledge on the subject.